EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE GI DAN NHT DALAM LC7E TERHADAP PRESTASI BELAJAR MATEMATIKA DAN MOTIVASI BERPRESTASI DITINJAU DARI ADVERSITY QUOTIENT - Prihatiningrum, Wahyu; Budiyono, Budiyono; Riyadi, Riyadi (Jurnal Pembelajaran Matematika, 2014)
Abstract : The aim of this research was to determine the effect of learning models toward the learning achievement in Mathematics and the achievement motivation viewed from the Adversity Quotient (AQ). The learning models compared were Cooperative Learning Model of Group Investigation (GI) Type and Numbered Head Together (NHT) Type in Learning Cycle 7E (LC7E). This research used the quasi experimental research method. Its population was all of the students in Grade VII of State Junior Secondary Schools of Sukoharjo. The samples of the research were taken by using the stratified cluster random sampling technique. The samples consisted of 214 students, and they were divided into two groups, 107 students in Experimental Class 1 and 107 in Experimental Class 2. The instruments used for gathering the data of the research were test of achievement in Mathematics learning, questionnaire of achievement motivation, and AQ measurement tool. The data was analyzed using multivariate analysis of variance. The results of the research show that: (1) the students exposed to the NHT in LC7E have a better learning achievement in Mathematics than GI in LC7E; (2) the students exposed to the NHT in LC7E have a better achievement motivation than GI in LC7E; (3) the students with AQ of the climbers type have a better learning achievement in Mathematics than those the campers or quitters type, and the students with AQ of the campers type have a better learning achievement in Mathematics than those the quitters type; (4) the students with AQ of the climbers type have a better achievement motivation than the campers or quitters type, and the students with AQ of the campers type have a better achievement motivation than those the quitters type; (5) in each learning model, either in the NHT in LC7E or GI in LC7E, the students with AQ of the climbers type have a better learning achievement in Mathematics than those the campers or quitters type, and the students with AQ of the campers type have a better learning achievement in Mathematics than those the quitters type; (6) in each learning model, either the NHT in LC7E or the GI in LC7E, the students with AQ of the climbers type have a better achievement motivation than those the campers or quitters type, and the students with AQ of the campers type have a better achievement motivation than those the quitters type; (7) in each type of the AQ, either the quitters, campers, or climbers, the students exposed to the NHT in LC7E have a better learning achievement in Mathematics than GI in LC7E; and (8) in each type of the AQ, either the quitters, campers, or climbers, the students exposed to the NHT in LC7E have a better achievement motivation than GI in LC7E.Keywords: NHT, GI, learning cycle, adversity quotient, and achievement motivation.